Problematika Naskah Sejarah di Dunia Melayu: Antara Mitos dan Realita (Studi Kasus Hikayat Raja Pasai) - 'Afifah, Nurul (Universitas Negeri Yogyakarta, 2024)
One of the challenges that historians and philologists face is analyzing historical texts, especially traditional historiographic works like 'babad' and 'hikayat,' which may have been added to or subtracted from in various aspects. Such manuscripts cannot be considered the primary reference source for constructing a chronological history, as they lean more towards historical literature constructed from the author's imagination. This article discusses the challenges posed by Malay manuscripts that contain elements of myth and imagination. The study takes a case example of the manuscript